The determinant of a mobile wallet intention among consumers / Mohd Syazwan Mohd Noor - Mohd Noor, Mohd Syazwan (Faculty of Business and Management, 2020)
The research was providing information about the determinants of a mobile wallet among consumers. As we know that in recent years, mobile wallet has become more popular but not of the people like to use a mobile wallet. According to Chatterjee & Bolar (2019) the reason why people didn’t use a mobile wallet because of perceived ease of use, compatibility, perceived behavioural control, and trusts. The objective of this research is to determine the level of consumers’ awareness toward a mobile wallet intention. The second is to examine the relationship between perceived ease of use with behavioural intention to use a mobile wallet. The third is to investigate the relationship between compatibility with behavioural intention to use a mobile wallet. The fourth is to research the prior perceived behavioural control with behavioural intention to use a mobile wallet. The fifth is to identify the relationship between trusts with behavioural intention to use a mobile wallet. All the data collection will be analysed using Statistical Package for Social Science (SPSS). In general, the results of this study show that trusts is most important element toward behavioural intention to use a mobile wallet. Method of collection data are primary and secondary data such as questionnaire, text books, journals, articles, newspaper and related with it. Researcher used questionnaire as a main instrumental in data collection method and involves 80 respondents among workers in Overseas Chinese Banking Corporation under Card Operations Department. The conclusion for this study is from the outcome of finding and analysis. Recommendations for future research have been discussed in final chapters.